Determinants of Caregiver Burden in Stroke Survivors who Underwent Decompressive Craniectomy - Karnam Anand; Sai Sirisha; Sanjana Putta; Sudhindra Vooturi; Manas Panigrahi; Sita Jayalakshmi; Subhash Kaul (Annals of Indian Academy of Neurology, 2024)
Background and Objectives: For stroke survivors (SS) who undergo decompressive craniectomy (DC), quality of life is intertwined with the care they receive. Burden on caregiver becomes an important determinant of recovery of SS. In this study, we aimed to analyze the determinants of burden on caregivers of SS who undergo DC. Methods: Caregivers of 198 SS who underwent DC formed the study population of this prospective observational study. The study was conducted in a tertiary referral unit between September 2019 and March 2021. Caregiver burden was quantified using Zarit Burden Interview. Analysis for association between the reported burden and modified Rankin Scale (mRS) score was done. Results: Mean age of the participants was 47.00 ± 11.2 years. The mRS outcome was poor in SS aged >60 years, Glasgow coma scale (GCS) score at presentation of <8, and in SS with bilateral/dominant hemisphere involvement. Outcome was better when DC was done ≤48 h (74.2% vs. 47.2%, P < 0.001) and if SS were shifted to a rehabilitation unit. Among caregivers, 58% and 16% reported to be always and frequently burdened, respectively; 33.3% of caregivers considered a retrospective review of consent for DC. A higher mRS score was associated with more burden. Conclusion: Early DC and care at rehabilitation unit were associated with better functional outcomes in SS. Nearly 75% of caregivers of patients post-DC reported high burden of providing care to SS, and the burden increased linearly with mRS score.